2020
DOI: 10.1136/bmj.m2282
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and covid-19

Abstract: Public Health England's review of disparities in covid-19 is a serious missed opportunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 2 publications
1
84
1
1
Order By: Relevance
“…US counties with majority black residents showed three times the rate of COVID-19 cases and six times the rate of deaths as counties with majority white residents (27). A study conducted in the UK similarly found that mortality rates in COVID-19 patients were twice as high in Bangladeshi communities and 10-50% higher in other ethnic minority communities when compared to the white British population (28).…”
Section: Demographics Related Factors In Sle and Covid-19mentioning
confidence: 93%
“…US counties with majority black residents showed three times the rate of COVID-19 cases and six times the rate of deaths as counties with majority white residents (27). A study conducted in the UK similarly found that mortality rates in COVID-19 patients were twice as high in Bangladeshi communities and 10-50% higher in other ethnic minority communities when compared to the white British population (28).…”
Section: Demographics Related Factors In Sle and Covid-19mentioning
confidence: 93%
“…The delay was discussed on June 25th, 2020, at a London Assembly Health Committee enquiry, 5 during which one of the authors of the report, Dr Kevin Fenton, was unable to offer any reason for the hold up once the report had been submitted to Government ministers. In a June 11th British Medical Journal editorial, moreover, Patel et al (2020) described the government's lack of attention to ethnic disparities as a 'serious missed opportunity' to address ethnic disparities. This reflected the curious condition of a historically specific post-racial period marking the morbidity of UK race politics where race is a public issue but also being concealed or hidden at the same time.…”
Section: Political Morbiditiesmentioning
confidence: 99%
“…Many other professionals important to the mental health care of people with intellectual disabilities and developmental disorders, such as those working in primary care and pharmacists, were not included in the sample. Future work should also aim to increase participation rates of non-white staff groups given what is now known about the impact of COVID-19 on their overall health and their importance as key workers (Patel et al 2020).…”
Section: Limitationsmentioning
confidence: 99%